Ru-Co co-doped Ti / SnO2-Sb anode and preparation method and application thereof

By using Ru-Co co-doped Ti/SnO2-Sb anodes, the problems of insufficient catalytic activity and stability of anode materials were solved, achieving efficient electrocatalytic degradation of organic pollutants, extending service life and reducing production costs.

CN120903648APending Publication Date: 2025-11-07NANJING UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511344458.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing anode materials have insufficient catalytic activity and poor stability, making it difficult to effectively remove highly toxic and recalcitrant organic pollutants from industrial wastewater. Furthermore, their preparation processes are complex and costly.

Method used

A Ru-Co co-doped Ti/SnO2-Sb anode was used. By adjusting the molar ratio of Ru and Co, a stable solid solution was formed, the electronic structure of the catalyst layer was optimized, and the catalytic activity and mechanical stability were improved. The preparation method includes steps such as precursor solution coating, drying and calcination.

Benefits of technology

It significantly improves the electrocatalytic degradation efficiency of organic pollutants, extends the service life of the anode, reduces production costs, and is suitable for large-scale manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120903648A_ABST
    Figure CN120903648A_ABST
Patent Text Reader

Abstract

The invention discloses a Ru-Co co-doped Ti / SnO2-Sb anode as well as a preparation method and application thereof, and belongs to the technical field of electro-catalysis wastewater treatment. The catalyst comprises a titanium-containing substrate material and a catalyst loaded on the substrate material, the catalyst comprises Ru and Co, and the molar ratio of the Ru to the Co is (1-3): (1-3); the catalyst also comprises Sn and Sb, and the Sn, Sb, Ru and Co are loaded on the substrate material to form a catalyst layer. Wherein Ru and Co have a synergistic effect, and the prepared catalyst has extremely high electrocatalytic degradation performance and structural stability of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of electrocatalytic wastewater treatment, and more particularly relates to a Ru-Co co-doped Ti / SnO2-Sb anode and a preparation method and application thereof. BACKGROUND

[0002] With the continuous advancement of industrialization, the amount of industrial wastewater discharge is increasing, which often contains a large amount of highly toxic and difficult-to-degrade organic pollutants, bringing severe challenges to environmental governance. Traditional physical and biological treatment technologies often fail to achieve ideal removal effects on such pollutants. The electrocatalytic oxidation technology can generate strong oxidizing •OH in situ at normal temperature and pressure, realizing efficient degradation and even complete mineralization of organic pollutants. In addition, the technology has the advantages of green environmental protection, no need to add chemical reagents, no secondary pollution, compact equipment structure, and easy automation control, showing broad application prospects.

[0003] Anode material is the core of electrocatalytic oxidation technology, and its performance directly affects the pollutant removal efficiency, system operation stability and energy consumption level. Currently, commercial anode materials can be roughly divided into two categories: one is active anode, such as graphite, Ti / Pt, Ti / RuO2-IrO2 anode, which has high stability, but the generated •OH is in a chemisorbed state and has strong interaction with the anode, and has limited oxidation ability for organic matter; the other is non-active anode, such as Ti / SnO2-Sb, Ti / PbO2 and BDD anode, the generated •OH is mostly in a physisorbed state and has higher reactivity, which is suitable for deep degradation of organic matter. However, Ti / SnO2-Sb and Ti / PbO2 anodes have problems such as poor stability, easy peeling of catalytic layer and short service life; while BDD anode has excellent performance, but its preparation process is complex and the cost is high, which limits its popularization in engineering application.

[0004] Therefore, it has become a key problem to be solved in the current electrocatalytic wastewater treatment technology field to develop an anode material with high catalytic activity, stable structure, long service life, simple preparation process and low cost. SUMMARY

[0005] 1. Problem to be solved In view of the problems of insufficient catalytic activity and poor stability of the anode material in the prior art, the first object of the present application is to provide a Ru-Co co-doped Ti / SnO2-Sb anode. The second object of the present application is to provide a preparation method of the Ru-Co co-doped Ti / SnO2-Sb anode. The third object of the present application is to provide an application of the Ru-Co co-doped Ti / SnO2-Sb anode.

[0006] 2. Technical solution To solve the above problems, the technical solution adopted by the present application is as follows: In a first aspect of the present application, a Ru-Co co-doped Ti / SnO2-Sb anode is provided, comprising: a base material and a catalyst supported on the base material; The catalyst comprises an oxide of Ru and an oxide of Co. The oxide of Ru comprises RuO2. The oxide of Co comprises one or more of CoO, Co2O3 and Co3O4.

[0007] The molar ratio of the Ru element to the Co element is (1-3):(1-3).

[0008] Preferably, the molar ratio of the Ru element to the Co element is 1:1.

[0009] It should be noted that when the molar ratio of the Ru element to the Co element is greater than 3:1 or less than 1:3, i.e., the content of Ru element in the catalytic layer is significantly higher than that of Co element or significantly lower than that of Co element, the performance of the catalytic layer is affected. Specifically, when the molar ratio of the Ru element to the Co element is greater than 3:1, i.e., the content of Ru element in the catalytic layer is significantly higher than that of Co element: Ru helps to improve the compactness and conductivity of the coating, enhances the bonding force between the coating and the substrate, and endows the anode with better physical stability; however, too high a proportion of Ru tends to enhance the occurrence of oxygen evolution side reactions, occupy active sites of the anode, and reduce the generation of •OH, thereby weakening the oxidation selectivity of organic matter and leading to a decrease in pollutant removal rate. When the molar ratio of Ru to Co is less than 1:3, i.e., the content of Co in the catalytic layer is significantly higher than that of Ru: Co can form high-valence Co active centers in electrochemical reactions, which is conducive to promoting the generation of •OH and thus accelerating the oxidation degradation of organic matter; however, too high a proportion of Co will produce unstable oxide phase migration during repeated operation of the anode, causing local phase separation or the formation of particle-rich areas, leading to an increase in surface roughness and the intensification of micro-cracks of the catalytic layer, and further causing local shedding or a decrease in the bonding force of the catalytic layer, ultimately affecting the mechanical stability and service life of the anode. 4+

[0010] Therefore, by adjusting the Ru-Co ratio, the electronic structure of the catalytic layer is optimized, in which the electronegativity and potential of Ru are higher, which can guide the reasonable distribution of electrons between Ru-Co oxides, optimize the electronic structure of the coating, inhibit the electrode breakdown or local corrosion caused by local current concentration, and further improve the corrosion resistance of the whole layer system.

[0011] ​In addition, in addition to improving the overall mechanical stability of the electrode, the application also significantly improves the electrocatalytic selectivity and the ability to generate •OH. By adjusting the Ru-Co ratio, the electronic structure of the catalyst layer is optimized, which increases the generation rate of •OH while suppressing the occurrence of oxygen evolution side reactions, effectively improving the mineralization efficiency of pollutants.

[0012] According to any embodiment of the first aspect of the application, the catalyst further comprises an oxide of Sn and an oxide of Sb, and the molar ratio of Sn, Sb, Ru and Co is (120-240):(6-10):(1-3):(1-3).

[0013] According to any embodiment of the first aspect of the application, the loading amount of the catalyst on the Ti substrate material is 1.2-3.0 mg / cm 2 .

[0014] According to any embodiment of the first aspect of the application, the catalyst loaded on the substrate material forms a catalyst layer, and the catalyst comprises: an oxide of Co, an oxide of Ru, further comprising an oxide of Sn and an oxide of Sb, and the oxide of Ru and the oxide of Co are loaded on the substrate material.

[0015] wherein Ru and Co exist as oxides and are doped into the SnO2 lattice in the form of solid solution.

[0016] The above Ru and Co doping increases the electron cloud density around Sn and increases the Sb 5+ / Sb 3+ ratio, thereby increasing the concentration of charge carriers, increasing the vacancy oxygen / lattice oxygen ratio, and thus increasing the electrocatalytic activity.

[0017] Specifically, for the Ru and Co doping, the electron cloud density around Sn is increased: after Ru and Co doping, a stable metal-oxygen-metal bond structure is formed with Sn, significantly increasing the electron enrichment degree around Sn, thereby enhancing the electron transport capacity of the electrode for pollutants and promoting the oxidation reaction; for increasing the Sb 5+ / Sb 3+ ratio: Ru and Co doping can induce an increase in the valence state of Sb 5 + in the catalyst layer, thereby increasing the semiconductor carrier concentration, reducing the charge transport resistance, and improving the overall conductivity; For improving the ratio of vacant oxygen / lattice oxygen: Ru, Co doping induces the formation of oxygen defects in the catalytic layer, increasing the surface vacant oxygen, which as active sites can promote the generation of •OH radicals, thereby significantly enhancing the electrocatalytic degradation ability of organic pollutants.

[0018] In addition, the above-mentioned Ru and Co doping can improve the electrochemical stability of the electrode, so that it is not easy to be corroded at high voltage, prolonging the service life: RuO2 and SnO2 are both rutile-type tetragonal structures, with consistent crystal symmetry, and Ru 4+ is highly compatible with Sn 4+ in ionic radius and valence state, so Ru 4+ can effectively replace Sn 4+ into the SnO2 crystal lattice to form a stable solid solution, significantly improving the structural density and lattice stability of the catalytic layer, and further enhancing the mechanical strength and electrocatalytic performance of the anode material.

[0019] By constructing a Ru-Co bimetallic synergistic stabilization system, Co can form a stable oxide phase under oxidation conditions, with excellent structural rigidity and electrical conductivity, and can exist stably in the catalytic layer and enhance the film formation quality. At the same time, the introduction of Co can promote the refinement of SnO2 grains and enhance the density of the catalytic layer. Ru enhances the bonding strength between the catalytic layer and the substrate, and effectively inhibits the oxidation and dissolution of the coating at high potential. The synergistic effect of the two can construct a continuous and low-defect composite oxide network, significantly improve the corrosion resistance and anti-peeling performance, and avoid the formation of unstable CoO x under high Co content.

[0020] Compared with the Ni-Ru doping system used in patent 202411054840.6, Ni is mainly used to improve the electrocatalytic activity, and Ru is used to enhance the stability of the coating. However, Ni is a soft metal, which is prone to grain coarsening, morphology migration and particle agglomeration under high current density or long-term operation conditions, resulting in uneven composition and structure on the surface of the catalytic layer, and further causing local peeling, mechanical stability decline and corrosion resistance decay. In the Ru-Co doping system used in this application, Co replaces Ni as a synergistic element, which not only can promote the generation of •OH through the formation of high-valence Co 4+ active centers to improve the oxidation ability of organic matter, but also can significantly inhibit grain coarsening and morphology migration during operation due to the higher hardness and lattice stability of Co than Ni; at the same time, Ru provides excellent chemical stability and electrical conductivity, and the two form a stable multi-phase composite oxide structure in the coating, effectively improving the density, bonding strength and corrosion resistance of the catalytic layer, and significantly prolonging the service life of the anode.

[0021] In a second aspect, the present application provides a preparation method of the Ru-Co co-doped Ti / SnO2-Sb anode as described above, comprising the steps of: S1, precursor solution coating: uniformly brushing the precursor solution containing Sn, Sb, Ru and Co onto the base material; S2, drying and fixing: drying the base material after coating; S3, calcination: calcining the dried base material; wherein the steps S1-S3 are repeated N times to obtain the Ru-Co co-doped Ti / SnO2-Sb anode. According to any embodiment of the second aspect of the present application, the method further comprises the step of base material pretreatment: performing pickling and etching treatment on the base material to obtain the pretreated base material.

[0022] According to any embodiment of the second aspect of the present application, the pickling step is to place the base material in a mixed acid solution of HF and HNO3 for treatment to remove the oxide layer and impurities on the surface of the base material.

[0023] According to any embodiment of the second aspect of the present application, the volume ratio of the mixed acid solution is HF:HNO3:H2O = (1-2):(4-8):(5-10), preferably the volume ratio of the mixed acid solution is HF:HNO3:H2O = 1:4:5, the pickling time is 30-60 s, and the treatment temperature is room temperature.

[0024] According to any embodiment of the second aspect of the present application, the etching treatment is to perform acid etching on the pickled base material by using an acidic solution to form a micro-rough structure on the surface of the base material and improve the adhesion performance of the subsequent coating.

[0025] According to any embodiment of the second aspect of the present application, the acid for the etching treatment is one or more of oxalic acid, nitric acid, hydrochloric acid and sulfuric acid. According to any embodiment of the second aspect of the present application, the etching time is 30-60 min, and the treatment temperature is 80-95℃.

[0026] Preferably, the acidic solution is an oxalic acid solution. Preferably, the mass fraction of the oxalic acid solution is 8-12%.

[0027] According to any embodiment of the second aspect of the present application, in the step S2, the molar ratio of Sn, Sb, Ru and Co in the precursor solution is (120-240):(6-10):(1-3):(1-3). For example, the molar concentration of Sn in the precursor solution can be 400-500 mM; The molar concentration of Sb in the precursor solution can be 10-30 mM; The molar concentration of Ru in the precursor solution can be 2.5-10 mM; The molar concentration of Co in the precursor solution can be 2.5-10 mM.

[0028] According to any embodiment of the second aspect of the present application, the precursor solution containing Sn, Sb, Ru and Co is obtained by dissolving a compound containing Sn, a compound containing Sb, a compound containing Ru and a compound containing Co.

[0029] According to any embodiment of the first aspect of the present application, the compound containing Sn in the precursor solution is one or more of a metal chloride salt, a metal nitrate salt and a metal carbonate salt containing Sn; The compound containing Sb is one or more of a metal chloride salt, a metal nitrate salt and a metal carbonate salt containing Sb; The compound containing Ru is one or more of a metal chloride salt, a metal nitrate salt and a metal carbonate salt containing Ru; The compound containing Co is one or more of a metal chloride salt, a metal nitrate salt and a metal carbonate salt containing Co; Preferably, the metal salts are all metal chloride salts.

[0030] According to any embodiment of the second aspect of the present application, the solvent of the precursor solution is one or more of ethanol, isopropanol and n-butanol; Preferably, the solvent is isopropanol.

[0031] According to any embodiment of the second aspect of the present application, in the step S2, the temperature of the drying treatment is 80-95 ℃ and the time is 5-20 min.

[0032] According to any embodiment of the second aspect of the present application, in the step S3, the calcination temperature is 400-700 ℃, the time is 5-240 min, and the calcination atmosphere is an air atmosphere.

[0033] According to any embodiment of the second aspect of the present application, in the step S3 of the first N-1 times, the calcination temperature is 400-700 ℃, the time is 5-20 min, and N is 10-20; According to any embodiment of the second aspect of the present application, in the step S3 of the Nth time, the calcination temperature is 400-700 ℃, and the time is 1-4 h.

[0034] The Nth calcination is an annealing step, and the value of N changes the quality of the catalyst layer.

[0035] A third objective of this invention is to provide an application of the Ru-Co co-doped Ti / SnO2-Sb anode described above, or the Ru-Co co-doped Ti / SnO2-Sb anode prepared by the above method, in wastewater treatment.

[0036] According to any embodiment of the third aspect of the present invention, the wastewater is one or more of nitrification wastewater, pharmaceutical wastewater, coking wastewater, or dyeing and printing wastewater.

[0037] 3. Beneficial effects (1) The Ru-Co co-doped Ti / SnO2-Sb anode of the present invention has significant advantages in terms of structural stability and corrosion resistance: Co can promote the grain refinement of SnO2 coating during film formation, making its structure dense and uniform, and reducing the formation of microcracks and pore defects; Ru provides excellent chemical stability and lattice matching, significantly enhancing the bonding force between the coating and the titanium substrate, and inhibiting the oxidation and dissolution of the coating at high potential; the Ru-Co synergistic effect can construct a stable multiphase composite oxide system, effectively suppressing the unstable CoO that is easily generated when the Co ratio is high. x The phase allows Co to exist as a stable oxide phase under oxidizing conditions, which improves the density and anti-stripping ability of the catalyst layer, significantly delays the anode deactivation process, and thus improves its durability and reliability in complex aquatic environments. (2) The Ru-Co co-doped Ti / SnO2-Sb anode of the present invention exhibits excellent performance in the electrocatalytic degradation of organic pollutants: the introduction of Co can generate more high-valence Co on the anode surface. 3+ / Co 4+ The active center significantly enhances the generation rate of •OH, thereby improving the oxidation efficiency of recalcitrant organic compounds; Ru possesses excellent electrical conductivity, which can accelerate the electron transport rate within the catalyst layer and reduce energy loss during electron transport; the synergistic effect of the two not only increases the electron cloud density around Sn but also improves the oxidation efficiency of Sb. 5+ / Sb 3+ The ratio of oxygen vacancy to lattice oxygen is increased, thereby improving the carrier concentration; at the same time, the ratio of vacant oxygen to lattice oxygen is increased, further enhancing the electrocatalytic activity of the electrode surface, thus achieving efficient and stable electrocatalytic degradation of organic matter; (3) In the above-mentioned method for preparing Ru-Co co-doped Ti / SnO2-Sb anode of the present invention, the steps of precursor preparation, brushing, drying, and calcination are simple and easy to control, the process conditions are mild, there is no need to rely on complex and expensive equipment, and the repeatability and consistency are good. The entire preparation process is suitable for direct implementation on existing production lines, which facilitates large-scale continuous manufacturing, helps to reduce production costs and ensure product quality stability; (4) In the application of the above-mentioned Ru-Co co-doped Ti / SnO2-Sb anode in wastewater treatment, compared with the traditional Ti / SnO2-Sb anode, the COD removal efficiency of the industrial wastewater such as nitration, pharmaceutical, coking or printing and dyeing can be increased by 35-60%, and the service life can be increased by 10-20 times. BRIEF DESCRIPTION OF DRAWINGS

[0038] The technical solutions of the present application will be further described in detail below in combination with the drawings and examples, but it should be understood that these drawings are designed only for explanatory purposes, and therefore do not limit the scope of the present application. In addition, unless specifically indicated, these drawings are only intended to conceptually illustrate the structural configuration described herein, and do not necessarily be drawn to scale.

[0039] Figure 1 The scanning electron microscope image of the anode material prepared in Example 1 and Comparative Examples 1-3 of the present application; Figure 2 The Mott-Schottky curve of the anode material prepared in Example 1 and Comparative Examples 1-3 of the present application; Figure 3 The AC impedance curve of the anode material prepared in Example 1 and Comparative Examples 1-3 of the present application; Figure 4 The linear voltammetry scan curve of the anode material prepared in Example 1 and Comparative Examples 1-3 of the present application; Figure 5 The Tafel curve of the anode material prepared in Example 1 and Comparative Examples 1-3 of the present application; Figure 6 The XRD graph of the anode material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0040] The following detailed description of exemplary embodiments of the present application refers to the accompanying drawings, that form a part of this description, and in which are shown, by way of example, exemplary embodiments in which the present application can be practiced. While these exemplary embodiments are described in sufficient detail to enable those skilled in the art to practice the present application, it should be understood that other embodiments can be realized and that various changes can be made to the embodiments described herein without departing from the spirit and scope of the present application. The following detailed description of embodiments of the present application is not intended to limit the scope of the claimed application, but is merely intended to describe exemplary embodiments of the present application for illustrative purposes and not limit the description of the features and characteristics of the present application to the best mode contemplated for carrying out the present application, and to sufficiently enable one skilled in the art to practice the present application. Accordingly, the scope of the present application is defined only by the appended claims.

[0041] It should be understood that the following description is merely directed to describe one or several specific embodiments of the present application and does not strictly limit the scope of protection specifically requested by the present application.

[0042] Test method Loading: the calculation formula of the loading of the catalytic layer in the embodiments of the present application is:

[0043] The specific conditions not specified in the following examples are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used are not specified by the manufacturer, and are conventional products that can be obtained by market purchase.

[0044] Mott-Schottky curve test conditions: instrument model used: 760e electrochemical workstation of Shanghai Chenhua Company; reference electrode: Ag / saturated AgCl electrode; counter electrode: Pt electrode; working electrode: prepared anode material; electrolyte is 0.05 mol / L Na2SO4 solution, scanning speed is 10 mV / s, potential window is 0.6~1.4 V vs. RHE, test frequency is 10 3 ~10 4 Hz, amplitude is 10 mV.

[0045] AC impedance test conditions: instrument model used: 760e electrochemical workstation of Shanghai Chenhua Company; reference electrode: Ag / saturated AgCl electrode; counter electrode: Pt electrode; working electrode: prepared anode material; electrolyte is 0.0025 mol / L K3[Fe(CN)6] solution, test frequency is 10 -1 ~10 6 Hz, amplitude is 5 mV.

[0046] Linear voltammetry curve and Tafel curve test conditions: instrument model used: 760e electrochemical workstation of Shanghai Chenhua Company; reference electrode: Ag / saturated AgCl electrode; counter electrode: Pt electrode; working electrode: prepared anode material; electrolyte is 0.05 mol / L Na2SO4 solution, scanning speed is 10 mV / s, potential window is 1~3.5 V vs. RHE.

[0047] Example 1 (1) A Ru-Co co-doped Ti / SnO2-Sb anode, comprising: a titanium-containing base material and a catalyst loaded on the base material; the catalyst comprises an oxide of Ru, an oxide of Co, an oxide of Sn and an oxide of Sb; the molar ratio of the Co element and the Ru element is 1:1; The molar ratio of Sn, Sb, Ru, and Co is 180:8:2:2.

[0048] The loading of the catalyst is 2 mg / cm 2 and is recorded as Ti / SnO2-Sb-Ru-Co.

[0049] (2) Base pretreatment: the Ti base (Ti plate) is pickled in a mixed acid solution with a volume ratio of HF:HNO3:H2O = 1:4:5 at room temperature for 45 s, and then is etched at 90 ℃ for 45 min using oxalic acid with a mass fraction of 10% to obtain a pretreated Ti base material; (3) A method for preparing a Ru-Co co-doped Ti / SnO2-Sb anode, comprising the steps of: S1, precursor solution coating: SnCl4·5H2O, SbCl3, RuCl2·3H2O, and CoCl2·6H2O are added to isopropanol, and the concentrations thereof are 450 mM, 20 mM, 5 mM, and 5 mM respectively, and are fully ultrasonically dissolved to obtain a catalytic layer precursor solution, and then the precursor solution is uniformly brushed onto the pretreated Ti base material; S2, drying and fixing: the base material after coating is dried at 90 ℃ for 10 min to fix the precursor solution into a film on the Ti base; S3, calcination: the dried Ti base material is calcined; Steps S1-S3 are repeated 15 times, and in the first 14 times, the calcination temperature in step S3 is 550 ℃, and the time is 10 min; in the 15th time, the calcination in step S3 is calcined at 550 ℃ for 2 h to prepare a Ru-Co co-doped Ti / SnO2-Sb anode, and the loading of the catalyst of the Ru-Co co-doped Ti / SnO2-Sb anode is 2 mg / cm 2 and is recorded as Ti / SnO2-Sb-Ru-Co, the scanning electron microscope image thereof is as shown in Figure 1 , the Mott-Schottky curve diagram is as shown in Figure 2 , the alternating current impedance curve diagram is as shown in Figure 3 , the linear voltammetry scan curve diagram is as shown in Figure 4 , the Tafel curve diagram is as shown in 5, and the XRD diagram is as shown in Figure 6 .

[0050] Example 2 The difference between this embodiment and Example 1 is that the concentration of RuCl2·3H2O is 2.5 mM, The molar ratio of the Co element and the Ru element is 2:1; The molar ratio of Sn, Sb, Co, and Ru is 180:8:2:1; The rest of the implementation conditions are unchanged. The final Ru-Co co-doped Ti / Sn02-Sb anode catalyst prepared has a loading of 2 mg / cm 2 .

[0051] Example 3 The difference between this example and Example 1 is that the concentration of RuCl2-3H2O is 7.5 mM, The molar ratio of the Co element and the Ru element is 2:3; The molar ratio of the Sn, Sb, Co, and Ru is 180:8:2:3; The rest of the implementation conditions are unchanged. The final Ru-Co co-doped Ti / Sn02-Sb anode catalyst prepared has a loading of 2 mg / cm 2 .

[0052] Example 4 The difference between this example and Example 1 is that the concentration of CoCl2-6H2O is 2.5 mM, The molar ratio of the Co element and the Ru element is 1:2; The molar ratio of the Sn, Sb, Co, and Ru is 180:8:1:2; The rest of the implementation conditions are unchanged. The final Ru-Co co-doped Ti / Sn02-Sb anode catalyst prepared has a loading of 2 mg / cm 2 .

[0053] Example 5 The difference between this example and Example 1 is that the concentration of CoCl2-6H2O is 7.5 mM, The molar ratio of the Co element and the Ru element is 3:2; The molar ratio of the Sn, Sb, Co, and Ru is 180:8:3:2; The rest of the implementation conditions are unchanged. The final Ru-Co co-doped Ti / Sn02-Sb anode catalyst prepared has a loading of 2 mg / cm 2 .

[0054] Example 6 The difference between this example and Example 1 is that the number of repetitions of steps S1-S3 is 10, and the rest of the implementation conditions are unchanged. The final Ru-Co co-doped Ti / Sn02-Sb anode catalyst prepared has a loading of 1.3 mg / cm 2 .

[0055] Example 7 The difference between this example and example 1 is only that the number of repeating steps S1-S3 is 20 times, and the rest of the implementation conditions are unchanged. The final prepared Ru-Co co-doped Ti / SnO2-Sb anode catalyst loading is 2.7 mg / cm 2 .

[0056] Example 8 The difference between this example and example 1 is only that the calcination temperature is 400 ℃, and the rest of the implementation conditions are unchanged. The final prepared Ru-Co co-doped Ti / SnO2-Sb anode catalyst loading is 2 mg / cm 2 .

[0057] Example 9 The difference between this example and example 1 is only that the calcination temperature is 700 ℃, and the rest of the implementation conditions are unchanged. The final prepared Ru-Co co-doped Ti / SnO2-Sb anode catalyst loading is 2 mg / cm 2 .

[0058] Comparative Example 1 The difference between this comparative example and example 1 is only that RuCl2·3H2O and CoCl2·6H2O are not added in the precursor solution, and the rest of the implementation conditions are unchanged. The final prepared anode catalyst loading is 2 mg / cm 2 , and is recorded as Ti / SnO2-Sb, the scanning electron microscope image thereof is shown in Figure 1 , the Mott-Schottky curve diagram is shown in Figure 2 , the alternating current impedance curve diagram is shown in Figure 3 , the linear voltammetry scan curve diagram is shown in Figure 4 , and the Tafel curve diagram is shown in 5.

[0059] Comparative Example 2 The difference between this comparative example and example 1 is only that RuCl2·3H2O is not added in the precursor solution, and the rest of the implementation conditions are unchanged. The final prepared anode catalyst loading is 2 mg / cm 2 , and is recorded as Ti / SnO2-Sb-Co, the scanning electron microscope image thereof is shown in Figure 1 , the Mott-Schottky curve diagram is shown in Figure 2 , the alternating current impedance curve diagram is shown in Figure 3 , the linear voltammetry scan curve diagram is shown in Figure 4 , and the Tafel curve diagram is shown in 5.

[0060] Comparative Example 3 The difference between this comparative example and example 1 is only that CoCl2·6H2O is not added in the precursor solution, and the rest of the implementation conditions are unchanged. The final prepared anode catalyst loading is 2 mg / cm 2and recorded as Ti / SnO2-Sb-Ru, the scanning electron microscope image thereof is shown in Figure 1, the Mott-Schottky curve thereof is shown in Figure 2, the alternating current impedance curve thereof is shown in Figure 3, the linear voltammetry scan curve thereof is shown in Figure 4, and the Tafel curve thereof is shown in Figure 5. Figure 1 Figure 2 Figure 3 Figure 4

[0061] Comparative Example 4 The difference between this comparative example and Example 1 is that SnCl4·5H2O and SbCl3 are not added in the precursor solution, and the rest of the implementation conditions are unchanged. The catalyst loading of the anode finally prepared is 0.02 mg / cm 2 .

[0062] Comparative Example 5 The difference between this comparative example and Example 1 is that the concentration of RuCl2·3H2O added is 1 mM, the molar ratio of the Co element and the Ru element is 2:4; the molar ratio of Sn, Sb, Co, and Ru is 180:8:2:4, and the rest of the implementation conditions are unchanged. The catalyst loading of the Ru-Co co-doped Ti / SnO2-Sb anode finally prepared is 2 mg / cm 2 .

[0063] Comparative Example 6 The difference between this comparative example and Example 1 is that the concentration of RuCl2·3H2O added is 25 mM, the molar ratio of the Co element and the Ru element is 2:10; the molar ratio of Sn, Sb, Co, and Ru is 180:8:2:10; and the rest of the implementation conditions are unchanged. The catalyst loading of the Ru-Co co-doped Ti / SnO2-Sb anode finally prepared is 2 mg / cm 2 .

[0064] Comparative Example 7 The difference between this comparative example and Example 1 is that the concentration of CoCl2·6H2O added is 1 mM, the molar ratio of the Co element and the Ru element is 4:2; the molar ratio of Sn, Sb, Co, and Ru is 180:8:4:2; and the rest of the implementation conditions are unchanged. The catalyst loading of the Ru-Co co-doped Ti / SnO2-Sb anode finally prepared is 2 mg / cm 2 .

[0065] Comparative Example 8 ​​​​The difference between the present comparative example and Example 1 is only that the concentration of CoCl2-6H2O added is 25 mM, and the rest of the implementation conditions are unchanged. The loading of the Ru-Co co-doped Ti / SnO2-Sb anode catalyst finally prepared is 2 mg / cm2. The molar ratio of the Co element and the Ru element is 10:2. The molar ratio of the Sn, Sb, Co, and Ru is 180:8:10:2. The rest of the implementation conditions are unchanged, and the loading of the Ru-Co co-doped Ti / SnO2-Sb anode catalyst finally prepared is 2 mg / cm2. 2 .

[0066] Comparative Example 9 The difference between the present comparative example and Example 1 is only that the number of repeating steps S1-S3 is 8 times, and the rest of the implementation conditions are unchanged. The loading of the Ru-Co co-doped Ti / SnO2-Sb anode catalyst finally prepared is 1.1 mg / cm2. 2 .

[0067] Comparative Example 10 The difference between the present comparative example and Example 1 is only that the number of repeating steps S1-S3 is 25 times, and the rest of the implementation conditions are unchanged. The loading of the Ru-Co co-doped Ti / SnO2-Sb anode catalyst finally prepared is 3.3 mg / cm2. 2 .

[0068] The anodes prepared in Examples 1-9 and Comparative Examples 1-10 were subjected to degradation experiments.

[0069] Degradation process: The electrocatalytic activity and service life of the anodes prepared in the above examples and comparative examples were tested using four kinds of industrial wastewater, namely nitration, pharmaceutical, coking, and printing and dyeing. Among them, the main pollutants in the nitration wastewater are nitroaromatic compounds such as o-nitrophenol and m-nitrophenol, and the COD is 14500 mg / L; the main pollutants in the pharmaceutical wastewater are various heterocyclic compounds such as pyridine and quinoline, and the COD is 16700 mg / L; the main pollutants in the coking wastewater are various phenols and polycyclic aromatic hydrocarbons such as phenol and naphthol, and the COD is 18200 mg / L; the main pollutants in the printing and dyeing wastewater are various dyes such as orange yellow G and rhodamine B, and the COD is 6400 mg / L. Stainless steel was used as the cathode, and repeated batch electrochemical oxidation experiments were carried out, with each batch reaction lasting 4 h, until the anode was deactivated, i.e. the internal resistance suddenly increased or the anode was corroded. The COD removal rate of the anode is the average COD removal rate of each batch; the service life is the total use time before the anode is deactivated, i.e. the number of batches x 4 h. The distance between the electrodes is 1 cm, the wastewater volume is 100 mL, and the current density is 30 mA / cm2. 2 .

[0070] Table 1 Degradation of anodes in Examples 1 and Comparative Examples 1-10 on different wastewaters

[0071] Table 2 Degradation of different anodes to different wastewater in different embodiments

[0072] According to the data of Example 1 and Comparative Examples 1-4 in Table 1, the Ru-Co co-doped Ti / SnO2-Sb anode is significantly superior to other single-doped or undoped anode materials in catalytic performance and service life. Co forms a large number of high-valence Co 3+ / Co 4+ active sites during doping, which can effectively catalyze water decomposition to generate •OH and accelerate the oxidation and degradation process of organic pollutants; Ru, as a noble metal oxide with excellent electrical conductivity, builds a continuous electron conduction channel in the catalytic layer, accelerating the transfer of electric charges at the anode interface, so that •OH can be efficiently released and utilized. Co can promote the refinement and ordered arrangement of SnO2-Sb grains during film formation, forming a dense and uniform coating structure, reducing internal micro-cracks and pore defects in the coating; Ru element helps to improve the adhesion between the catalytic layer and the Ti substrate, preventing the anode from peeling or falling off in a long-term strong oxidation environment, thereby significantly prolonging the service life of the anode.

[0073] According to the data of Examples 1-5 and Comparative Examples 5-8 in Tables 1 and 2, when the doping concentrations of Ru and Co are low, increasing the doping concentrations of Ru and Co appropriately can significantly improve the catalytic activity and service life of the anode. However, when the doping concentrations of Ru and Co continue to rise beyond a certain threshold, excessive metal loading may cause catalyst agglomeration or active site shielding on the anode surface, resulting in a decrease in reaction surface area, blocked electron migration channels, and a decrease in the catalytic degradation effect of organic matter. In addition, high metal loading may also introduce large residual stress in the catalytic layer, increasing the risk of coating cracking and peeling, thereby shortening the service life of the anode.

[0074] According to the data of Examples 1, 6, 7 and Comparative Examples 9, 10 in Tables 1 and 2, increasing the brushing times appropriately helps to increase the loading of the catalyst, making the catalytic layer more uniform and dense, thereby increasing the effective reaction area of the anode surface, improving the catalytic activity and stability of the anode, and thus improving the COD removal rate and service life. However, when the brushing times are too many, the catalytic layer is too thick, which may lead to a decrease in the electrical conductivity of the anode, an increase in internal stress accumulation, and a decrease in the adhesion between the catalyst layer and the substrate, which may cause peeling in long-term operation, thereby reducing the catalytic activity and service life of the anode.

[0075] From the data of Examples 1, 8, and 9 in Table 2, it can be seen that a suitable calcination temperature can promote the crystal combination and densification between Ru, Co and SnO2-Sb, effectively improving the structural stability and catalytic activity of the coating. However, when the calcination temperature is too low, the catalyst cannot be fully crystallized, resulting in a loose coating, poor adhesion, and affecting the catalytic performance and service life of the anode; while when the calcination temperature is too high, it may lead to large catalyst grain size, reduced grain boundary, and reduced catalytic active site density, while the thermal stress accumulation induced by high temperature will also accelerate the cracking of the coating, weakening the physical stability and electrochemical performance of the anode.

[0076] According to Figure 1 The scanning electron microscopy characterization results show that the Ti / SnO2-Sb anode surface without metal doping presents a clear crack-like mud texture structure. This structural defect is mainly due to the mismatch of the thermal expansion coefficients between the coating and the titanium substrate, and the stress concentration phenomenon of the coating caused by uneven surface tension during drying and calcination. After Ru or Co doping alone, the mud crack structure on the anode surface is alleviated, and the coating density and integrity are improved compared with the undoped sample, but local cracks and surface undulations can still be observed, indicating that single doping cannot completely eliminate the internal stress and defects of the coating. After Ru and Co are simultaneously and synergistically doped in the Ti / SnO2-Sb anode, the surface morphology has changed significantly, the original crack-like mud texture structure has basically disappeared, the coating has become more dense, flat and continuous, the particle size is uniform, and the interface is well combined. This significant improvement in surface morphology effectively reduces the crack propagation path, enhances the mechanical stability and electrochemical durability of the coating, and thus greatly improves the long-term service life and catalytic performance of the anode.

[0077] According to Figure 2 Mott-Schottky curves and Figure 3 The alternating current impedance spectroscopy results show that the Ru-Co co-doped Ti / SnO2-Sb anode has a higher carrier concentration and a lower charge transfer resistance than the undoped and single metal-doped Ti / SnO2-Sb anodes, improving the charge transfer rate of the electrochemical reaction on the anode surface.

[0078] According to Figure 4 Linear voltammetry scan curves and Figure 5 The Tafel curve results show that the Ru-Co co-doped Ti / SnO2-Sb anode has a significantly improved oxygen evolution potential and Tafel curve slope compared with the undoped and single metal-doped Ti / SnO2-Sb anodes, effectively inhibiting the oxygen evolution side reaction, improving the stability of the anode, and the catalytic degradation activity of organic pollutants.

[0079] Combining Figure 6The XRD pattern of the SnO2:Ru:Co shows that no new phase or impurity peak is observed except the characteristic diffraction peak of SnO2. The diffraction angle becomes larger and the lattice spacing decreases with the incorporation of Ru and Co. The above characterization shows that Ru and Co enter the SnO2 lattice to form a solid solution and cause lattice shrinkage without existing in the form of a single oxide.

[0080] The above description is merely preferred embodiments of the present application and the technical principles used, and those skilled in the art should understand that the scope of the present application is not limited to the technical solutions formed by the specific combinations of the above technical features, and should also cover other technical solutions formed by any combinations of the above technical features or equivalent features without departing from the inventive concept, such as technical solutions formed by replacing the above features with technical features disclosed in the present application (but not limited to) having similar functions.

[0081] In addition to the technical features described in the specification, the remaining technical features are known to those skilled in the art, and in order to highlight the innovative features of the present application, the remaining technical features will not be described here.

Claims

1. A Ru-Co co-doped Ti / Sn02-Sb anode, characterized in that, The application relates to a Ru-Co co-doped Ti / SnO2-Sb anode and a preparation method thereof. The application relates to a Ru-Co co-doped Ti / SnO2-Sb anode and a preparation method thereof. The application relates to a Ru-Co co-doped Ti / SnO2-Sb anode and a preparation method thereof. The Co oxide comprises one or more of CoO, Co2O3 and Co3O4. The Ru oxide comprises RuO2. The molar ratio of Co elements and Ru elements is (1-3):(1-3).

2. The Ru-Co co-doped Ti / Sn02-Sb anode according to claim 1, characterized in that The catalyst further comprises Sn oxide and Sb oxide, which are loaded on the substrate material together with the Ru oxide and the Co oxide to form a catalytic layer, wherein the Ru and the Co exist in the form of oxides and are doped into the SnO2 lattice in the form of solid solutions.

3. The Ru-Co co-doped Ti / Sn02-Sb anode according to claim 2, characterized in that The molar ratio of Sn elements, Sb elements, Co elements and Ru elements is (120-240):(6-10):(1-3):(1-3).

4. The Ru-Co co-doped Ti / Sn02-Sb anode of claim 2, wherein, The catalyst is loaded on the substrate material in an amount of 1.2 to 3.0 mg / cm 2 .

5. A method for the preparation of a Ru-Co co-doped Ti / Sn02-Sb anode according to any one of claims 1 to 4, characterized in that, The application relates to a Ru-Co co-doped Ti / SnO2-Sb anode and a preparation method thereof. S1, precursor solution coating: uniformly brushing a Co and Ru-containing precursor solution onto a substrate material; S2, drying and fixing: drying the substrate material after coating is completed; S3, calcining: calcining the dried substrate material; The steps S1-S3 are repeated N times to obtain the Ru-Co co-doped Ti / SnO2-Sb anode. In the step S1, the molar ratio of Ru elements and Co elements in the precursor solution is (1-3):(1-3).

6. The method of claim 5, wherein the Ru-Co co-doped Ti / Sn02-Sb anode is prepared by the steps of: The precursor solution further contains Sn elements and Sb elements, and the molar ratio of Sn elements, Sb elements, Co elements and Ru elements is (120-240):(6-10):(1-3):(1-3).

7. The preparation method of the Ru-Co co-doped Ti / SnO2-Sb anode according to claim 5 or 6, characterized in that, In the step S3, the calcining temperature is 400-700 DEG C, and the calcining time is 5-240 min; and / or, The value of N is 10-20; in the first N-1 times of the step S3, the calcining temperature is 400-700 DEG C, and the calcining time is 5-20 min; In the Nth time of the step S3, the calcining temperature is 400-700 DEG C, and the calcining time is 1-4 h.

8. The preparation method of the Ru-Co co-doped Ti / SnO2-Sb anode according to claim 7, characterized in that: The step of substrate pretreatment is further included, that is, the substrate material is polished, pickled and etched to obtain a pretreated substrate material; The pickling is to place the substrate material in a mixed acid solution of HF and HNO3 for treatment; And / or, The etching treatment is to perform acid etching on the pickled substrate material by using an acidic solution; And / or, The acid for the etching treatment is one or more of oxalic acid, nitric acid, hydrochloric acid and sulfuric acid.

9. The preparation method of the Ru-Co co-doped Ti / SnO2-Sb anode according to claim 8, characterized in that: In the step S2, the drying temperature is 80-95 DEG C, and the drying time is 5-20 min.

10. The use of a Ru-Co co-doped Ti / Sn02-Sb anode as claimed in any one of claims 1 to 4, or a Ru-Co co-doped Ti / Sn02-Sb anode prepared by the method of any one of claims 5 to 9, in the treatment of wastewater.

Citation Information

Patent Citations

  • Titanium-based nickel ruthenium bimetallic doped tin antimony electrode and preparation method and application thereof

    CN118908356A